The runaway midwife [large type] - Harman, Patricia, 1943- (Thorndike Press, 2017)
A USA Today Bestselling Author. Midwife Clara Perry is accustomed to comforting her pregnant patients, calming fathers-to-be, and delivering babies safely into the world. But when her life takes a nosedive, Clara realizes she hasn't been tending to her own needs and does something drastic: she runs away and starts over. On a tiny, remote Canadian island, Clara becomes Sara Livingston, a writer seeking solitude.